0.5x+2=0.3x+6

Simple and best practice solution for 0.5x+2=0.3x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.5x+2=0.3x+6 equation:


Simplifying
0.5x + 2 = 0.3x + 6

Reorder the terms:
2 + 0.5x = 0.3x + 6

Reorder the terms:
2 + 0.5x = 6 + 0.3x

Solving
2 + 0.5x = 6 + 0.3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.3x' to each side of the equation.
2 + 0.5x + -0.3x = 6 + 0.3x + -0.3x

Combine like terms: 0.5x + -0.3x = 0.2x
2 + 0.2x = 6 + 0.3x + -0.3x

Combine like terms: 0.3x + -0.3x = 0.0
2 + 0.2x = 6 + 0.0
2 + 0.2x = 6

Add '-2' to each side of the equation.
2 + -2 + 0.2x = 6 + -2

Combine like terms: 2 + -2 = 0
0 + 0.2x = 6 + -2
0.2x = 6 + -2

Combine like terms: 6 + -2 = 4
0.2x = 4

Divide each side by '0.2'.
x = 20

Simplifying
x = 20

See similar equations:

| 4x-3(7x-6)=-101 | | 2x(-1)=x-3 | | 3x-2y+5z=250 | | X+35=8x | | 8-9+7w=7w | | 25=z-4 | | 2x-7=-17+x | | A+(8+a)+a=125 | | -3x+6(-3x+5)=-75 | | 5x+3x-8=9(x-2) | | 9/2-2=d | | 3x+5(-3x+12)=-12 | | 7a^2+34a+40=0 | | 11-y=203 | | t+1-4t+8=8 | | b-1+3b=28 | | 3p+5=p+19 | | 51=-5x+3(6x-9) | | 4(3c-1)-1=10c+9 | | -4x+7(-x+8)=1 | | 8/2+1=c | | 6y+14+4=32 | | -3x-6(x+8)=60 | | -3pq+spr-7p-6=-6q-5 | | 2a+(a+87)=180 | | .3333x=9 | | -7x-2(-7x+2)=38 | | 5d-d-2d+3d=0 | | x^2-15x+82=0 | | -2x+-3x=15 | | 2(r-3)=4(-3r-5) | | 7xy+0=7xy |

Equations solver categories